2022
DOI: 10.3390/diagnostics12092193
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Associations between EEG Indices and Cognitive Deficits in Schizophrenia-Spectrum Disorders: A Systematic Review

Abstract: Cognitive dysfunctions represent a core feature of schizophrenia-spectrum disorders due to their presence throughout different illness stages and their impact on functioning. Abnormalities in electrophysiology (EEG) measures are highly related to these impairments, but the use of EEG indices in clinical practice is still limited. A systematic review of articles using Pubmed, Scopus and PsychINFO was undertaken in November 2021 to provide an overview of the relationships between EEG indices and cognitive impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 295 publications
(530 reference statements)
0
10
0
Order By: Relevance
“…Our results are also consistent with these studies. In addition, schizophrenic patients with attention deficits are prone to symptoms such as fantasies and cognitive disorders, which may be related to their lower gamma oscillations ( 47 , 48 ). Increased prefrontal gamma oscillations may be associated with the fact that musical rhythms and melodies increase patients’ interest and enhance auditory attention ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with these studies. In addition, schizophrenic patients with attention deficits are prone to symptoms such as fantasies and cognitive disorders, which may be related to their lower gamma oscillations ( 47 , 48 ). Increased prefrontal gamma oscillations may be associated with the fact that musical rhythms and melodies increase patients’ interest and enhance auditory attention ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…EEG beta rhythm oscillations play an important role in top-down signaling and feedback influences for cortical neurons that effectively support the precise synchronization of neuronal discharges [11,50]. Patients with schizophrenia were reported to have disturbances in both top-down signaling and EEG beta-band coordination [50].…”
Section: Discussionmentioning
confidence: 99%
“…There is convergent evidence that aberrant neural oscillations at low-and highfrequencies constitute an important aspect of the failure to generate coherent cognition, causing the characteristic cognitive deficits of schizophrenia [10,11]. These deficits are attributed to N-methyl-D-aspartate receptor hypofunction and could be assessed in schizophrenia patients with electroencephalography (EEG) [12].…”
Section: Introductionmentioning
confidence: 99%
“…As to task-related functional MRI, many studies found a decreased activation of the dorsomedial prefrontal cortex, the supplementary motor area, and the right inferior frontal gyrus during tasks involving neurocognitive processes and of the right angular gyrus during social-cognitive tasks [ 24 ]. Concerning EEG, abnormalities were found in alpha, theta and gamma activity, as well as in mismatch negativity and P300 waves, and were associated with impairments in different neurocognitive domains such as attention, working memory, visual and verbal learning, and executive functioning [ 32 ]. Finally, PET studies assessing brain glucose metabolism with 18-fluorodeoxyglucose evidenced a hypometabolism in the frontal cortex without significant alterations in other brain regions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%